Gastrointestinal stromal tumours (GIST)–development in pathology, surgery and medical therapy. Developed during the 10th German GIST-meeting, Göttingen - Agaimy, A.; Bauer, S.; Beham, A.; Bertolini, J.; Haller, F.; Koschny, R.; Maier, J.; Montemurro, M.; Perez, D.; Schaefer, I-M; Schildhaus, H-U; Wurst, C.; et al. (Zeitschrift für Gastroenterologie, 2015)
The first description of ligand-independent activating mutations in the KIT gene, which encodes the tyrosine-kinase KIT, greatly improved our understanding of gastrointestinal stromal tumour (GIST) biology. The therapeutic success in GIST has made tyrosine kinase inhibitors a "paradigm of targeted therapy". Deciphering resistance mechanisms in GIST has had implications for many other kinase-driven cancers. To exchange current knowledge within the field of GIST, the German GIST Meeting has taken place for now 10 years, traditionally in Göttingen. Subjects discussed include clinical diagnostics, pathology, surgery, and medical therapy. The following presentation gives an overview of the last meeting held in December 2013, including distinctive features in GIST and current data on the different topics.
EVALuna2:6707